Developing sociolinguistic context-based English-speaking materials for Islamic senior high school students - Susilawati, Endang (English Language Teaching Educational Journal, 2024)
This research was conducted for two purposes: (1) to describe the process of the design and development of English materials for conversation practices based on the sociolinguistic contexts for Grade X students at Islamic Senior High School Students (ISHS), and (2) to analyze the usability level of the product of materials’ development for the students. It is a study using research and development method which applied the stages of ADD out of ADDIE from Aldoobie, (2015) and Branch, R. M. (2009). The materials development focused on English-speaking materials in the form of conversation practices, which included the conversations of interpersonal and transactional communication whereby the sociolinguistic contexts are embedded. Additionally, communicative tasks were also presented for engaging students with the practice of the real English use. They were packed in the form a textbook which consisted of six units. The presentation of the materials in the units was following the features of CLT approach. The feasibility and the usability of the product was tested through internal validation using the three criteria (psychological, pedagogical, and content) of validity by Rubdy (2014). The result shows that the English-speaking materials are valid meaning usable for Grade X students of ISHS.